The Effect of Global Economic Uncertainty on Emerging Market Currencies : A Panel Data Analysis (Proceeding of The International Conference on Economics and Business, 2024)
Emerging market currencies are highly sensitive to global economic uncertainty. This study uses panel data analysis to explore the impact of external shocks, such as interest rate changes and geopolitical risks, on currency volatility in 10 emerging economies. Policy recommendations are offered to strengthen monetary stability and resilience.